PENGARUH KOMPETENSI MANAJERIAL DAN MOTIVASI BERPRESTASI TERHADAP KOMPETENSI PROFESIONAL GURU MADRASAH ALIYAH NEGERI PONTIANAK - Fatimah, Siti; Sukmawati, Sukmawati; Chiar, M. (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThe aimed of this research are to find out the influence of principal Islamic State SeniorHigh School in Pontianak for managerial competences and achievement motivation forprofessional teachers"™ competence. This research uses the quantitative approach withquestionnaires as the data collecting. The subject of this research are 55 teachers ofcivil servant/non-civil servant which is 26 to 60 years old, 29 female and malerespondens, having 2 years experienced and graduates of bachelor"™s degree (S1) ofIslamic State Senior High School in Pontianak. This sample using "Slovin" formula of10% Margin of Error. The result of this research (1) The competence of professionalteachers in Madrasah Aliyah Negeri in Pontianak have a good score with 52,7%; (2)The competence of principal Islamic Senior High School managerial also have a goodscore 45,5% ; (3) The descriptions of teacher achievements in Islamic State Senior HighSchool in Pontianak have a good score with 32,73%. So, the conclusion of thisresearch is the competence of professional teachers influencing by all competencevariables of principle of Islamic State Senior High School in Pontianak andachievement motivations with scoring 11,20% and 88,80% for another variables. Thisresearch could be applied to improve professional teachers competence in MadrasahAliyah Negeri in Pontianak.Keywords: Achievement Motivation, Competences, Managerial, Professional